2018
DOI: 10.1111/1460-6984.12434
|View full text |Cite
|
Sign up to set email alerts
|

Textual cohesion in oral narrative and procedural discourse: the effects of ageing and cognitive skills

Abstract: Background Knowledge of the discourse performance of non‐brain‐damaged individuals is critical not only for its differentiation from disordered expression but also for more accurate models of ageing and communication. The effect of ageing and cognitive skills on the cohesive adequacy of discourse has, until now, presented a confusing and ambiguous picture. Aims To examine comprehensively the effects of both age and cognitive skills on the discourse cohesion of 32 non‐brain‐damaged males divided into four age g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 72 publications
(90 reference statements)
2
11
1
2
Order By: Relevance
“…The hypothesis that cognition may be related to the discourse processing and also to education was considered due to studies that found that individuals who produced more consistent discourses obtained good performance on cognitive tasks and presented a higher level of education (Rogalski et al, 2010. Regarding to age, it was found that there was statistically difference between the group of young people and the group of elderly people only to the time of written production. This finding differs from other studies that have found that ageing significantly increased the number of cohesive errors and reduced the quantity of the referential ties in picture-sequence narratives (Sherratt & Bryan, 2019) and decreased discourse ability for cohesion and coherence (Babaei et al, 2019). Many factors could explain the differences between our and previous studies such as type (genre) of the discourse, our elderly group with subjects up to 75 years, and the stimulus (Bank Robbery picture) that apparently is easier than those described in other studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The hypothesis that cognition may be related to the discourse processing and also to education was considered due to studies that found that individuals who produced more consistent discourses obtained good performance on cognitive tasks and presented a higher level of education (Rogalski et al, 2010. Regarding to age, it was found that there was statistically difference between the group of young people and the group of elderly people only to the time of written production. This finding differs from other studies that have found that ageing significantly increased the number of cohesive errors and reduced the quantity of the referential ties in picture-sequence narratives (Sherratt & Bryan, 2019) and decreased discourse ability for cohesion and coherence (Babaei et al, 2019). Many factors could explain the differences between our and previous studies such as type (genre) of the discourse, our elderly group with subjects up to 75 years, and the stimulus (Bank Robbery picture) that apparently is easier than those described in other studies.…”
Section: Discussioncontrasting
confidence: 99%
“…At the same way, aging is a factor that can impact discourse production in several ways (Pistono, et al, 2017;Lira et al, 2018), and the effect of aging on the discourse has, until now, presented a confusing and ambiguous picture (Sherratt & Bryan, 2019). Some cognitive functions are influenced by age, and thus, they also impact the discourse production.…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, significant drawbacks to relying on picture descriptions, including limited richness and length (Ash et al, 2006), the somewhat unnatural nature of the task, and (in the case of the Cookie Theft picture) an outdated depiction of domestic life (Berube et al, 2019). Similarly, procedural recall places constraints on discourse but rarely occurs in everyday conversation and so can result in overly simplified speech (Sherratt and Bryan, 2019). By contrast, conversational speech is instinctive and naturalistic, though without constraints, samples can vary widely in length and content (Boschi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…2019), have also been shown to be vulnerable to age. Further, non‐uniform differences in some aspects of discourse production of older adults have been demonstrated with age (Sherratt and Bryan 2019). Measurable differences in some areas of cognitive and communication function due to age further supports the need for separate consideration of outcomes for older adults following a new‐onset TBI.…”
Section: Introductionmentioning
confidence: 99%